Comparative analysis of Gram's method and PAS for the identification of Candida spp. samples from the oral mucosa - Cátia Martins Leite Padilha; Bruna Lavinas Sayed Picciani; Bruna Michalski dos Santos; Arley Silva Júnior; Eliane Pedra Dias (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Candida species are part of the normal microbiota of healthy subjects, living as commensals. However, they can become pathogenic when changes in the mechanisms of host defense or disruption of anatomic barriers occur. Candidiasis is the most common fungal infection in the oral cavity, mainly caused by Candida albicans. The diagnosis is based on symptoms and clinical aspects, in association with laboratory methods. Objective: To evaluate the sensitivity and specificity of Gram's method for Candida spp. identification in scrapes from the buccal mucosa and evaluate the degree of concordance between clinical and cytological methods in the diagnosis of oral candidiasis. Material and methods: A blind study was performed in 170 smears from patients of Hospital Universitário Antônio Pedro of Universidade Federal Fluminense (HUAP/UFF), stained by Gram (n = 57), periodic acid-Schiff (PAS) (n = 57) and Papanicolaou (Pap) (n = 57) methods. Results: The comparative analysis of the methods demonstrated a higher prevalence of Candida spp. (12%) in PAS than in Gram staining, without statistic significance. The cytology method was positive in 93% of the clinical diagnosis of candidiasis. Conclusion: Gram was an adequate method; however more intensive professional training would be necessary to identify the fungus morphological structures. Although Pap test is the most common method of routine cytopathologic examination, for candidiasis diagnosis PAS staining is also recommended. Thus, it is suggested that candidiasis diagnosis should be accomplished by clinical evaluation in association with cytopathological analysis based on the identification of hyphae and/or pseudohyphae.